Associations between socioeconomic status and pregnancy outcomes: a greater magnitude of inequalities in perinatal health in Montreal than in Brussels - Mouctar Sow; Marie-France Raynault; Myriam De Spiegelaere (BMC, 2022)
Abstract Background Comparing health inequalities between countries helps us to highlight some factors specific to each context that contribute to these inequalities, thus contributing to the identification of courses of action likely to reduce them. This paper compares the associations between socioeconomic status (SES) and 1) low birth weight (LBW) and 2) preterm birth, in Brussels and Montreal (in general population, natives-born mothers, and immigrant mothers). Methods A population-based study examining associations between SES and pregnancy outcomes was conducted in each city, using administrative databases from Belgian and Quebec birth records (N = 97,844 and 214,620 births in Brussels and Montreal, respectively). Logistic regression models were developed in order to estimate the relationship between SES (maternal education and income quintile) and pregnancy outcomes, in each region. The analyses were first carried out for all births, then stratified according to the mother's origin. Results For the general population, SES is associated with LBW and preterm birth in both regions, except for income and preterm birth in Brussels. The association is stronger for mothers born in Belgium and Canada than for those born abroad. The main difference between the two regions concerns the magnitude of inequalities in perintal health, which is greater in Montreal than in Brussels among the general population. For native-born mothers, the magnitude of inequalities in perinatal health is also greater for mothers born in Canada than for those born in Belgium, except for the association between income and preterm birth. The socioeconomic gradient in perinatal health is less marked among immigrant mothers than native mothers. Conclusion Significant differences in inequalities in perinatal health are observed between Brussels and Montreal. These differences can be explained by : on the one hand, the existence of greater social inequalities in Montreal than in Brussels and, on the other hand, the lower vulnerability of immigrants with low SES in Brussels. Future studies seeking to understand the mechanisms that lead to inequalities in health in different contexts should take into account a comparison of immigration and poverty contexts, as well as the public policies related to these factors.